A public opinion propagation model for technological disasters - Yi Zhang; Wanjie Tang; Ting Ni (Scientific Reports)
Abstract Public opinion on technological disasters is influenced by unique factors and characteristics. Based on the infectious disease model, this paper develops a public opinion dissemination model for technological disasters, considering factors such as disaster severity, government response, accountability, and the impact of both positive and negative media content. Using differential equation stability theory, we analyze the existence and stability of both the free propagation equilibrium point and the propagation equilibrium point. The next-generation matrix method is applied to calculate the propagation threshold, revealing that disaster severity, government response, and accountability are key factors in the spread of public opinion. Sensitivity analyses examine how these key factors affect public opinion dynamics. A case study on the Shiyan gas explosion in Hubei Province is presented, with microblog data used to calculate model parameters. The proposed public opinion dissemination model is applied to this case and compared with two other models, demonstrating the viability and effectiveness of the developed model. The analyses also show that well-handled government responses can help calm public opinion, even in cases where accountability is lacking. Finally, policy suggestions are offered to enhance public opinion management during technological disasters.